0
$\begingroup$

I'm doing a bit of homework, and it says to prove or disprove the statement

$XZ+X'Y'+Y'Z'=XZ+Y'$

If you do a truth table and take the sum-of-products, you can eventually simplify the equation down to $XYZ+Y'$. Now that was way too close for me to stop there, and I couldn't think of anything beyond that. I plugged it into one of the WolframAlpha Boolean Algebra equators and it came out with $XYZ+Y'=XZ+Y'$. I'm perplexed as to how it got that, or if it's just a bug in the program.

The only thing I can think of is that it is an extension on the $A+A'B=A+B$ law, but I'm not entirely sure that can be used on $3$ different variables like this. Can someone explain if this is the legitimate answer, and if so can you please prove it so I can see how that's true? Thanks a bunch.

$\endgroup$
0
$\begingroup$

XZ + Y' = XZY +XZY' + Y' = XYZ + (XZY' +Y')
XZY' is a subset of Y'. So,
=XYZ + Y'

Best thing to do would be draw three intersecting circles as X,Y and Z and try to visualize LHS and RHS

$\endgroup$
0
$\begingroup$

Note that $\bar{Y} \implies X\bar{Y}Z$ and so $ \bar{Y} = X\bar{Y}Z + \bar{Y}$.

Then $ XYZ+ \bar{Y} = XYZ+ X\bar{Y}Z + \bar{Y}= X(Y+\bar{Y})Z + \bar{Y} = XZ + \bar{Y}$.

$\endgroup$
0
$\begingroup$

ABC + B’ = AC + B’ ?

The expression on the left means if B then AC, if not B then true. Obviously, the repeated mentioning of B is redundant, so the expression to the right, which reads if not B then true, else AC is its simplified equivalent. You can verify this by writing $B'+ABC=B'+BAC=$ $=(B'+B)(B'+AC)=1\cdot(B'+AC)=AC+B'.$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.